2018
DOI: 10.21147/j.issn.1000-9604.2018.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Cycle number of neoadjuvant chemotherapy might influence survival of patients with T1-4N2-3M0 nasopharyngeal carcinoma

Abstract: For N2-3 NPC, cycle number of NACT appeared to be an independent factor associated with an improvement of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
(18 reference statements)
3
19
0
Order By: Relevance
“…Moreover, 91.0% of the NPC‐related deaths had DM. By contrast, only 34.0% of them underwent LR It was in accordance with previous studies that DM, rather than LR, is the primary obstacle to treatment success in N2‐3 NPC patients . As we know, DM is mainly eradicated by chemotherapy.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, 91.0% of the NPC‐related deaths had DM. By contrast, only 34.0% of them underwent LR It was in accordance with previous studies that DM, rather than LR, is the primary obstacle to treatment success in N2‐3 NPC patients . As we know, DM is mainly eradicated by chemotherapy.…”
Section: Discussionsupporting
confidence: 87%
“…These studies established the optimal dose interval as 160‐240 mg/m 2 . In our hospital, the cisplatin dose of NACT was 60 mg/m 2 and 80 mg/m 2 in the TPF and the PF regimens, respectively . So the cumulative cisplatin dose for the patients of our study could reach ≥180‐240 mg/m 2 , which was showed to be effective in controlling DM.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Although the results were not entirely consistent, these studies corroborated the fact that additional more cycles of IC might not lead to better survival outcomes. In contrast to these three studies, the scholars in another study reported that the number of IC appeared to be an independent predictor and for N2-3 NPC, survival data of the 4 cycles of IC were better than those of 2 cycles [20]. It is noted that the study paid attention to advance N stage patients and lack of patient receiving 3 cycles of IC.…”
Section: Discussionmentioning
confidence: 82%
“…12 The Health-related quality of life (HR-QOL) assessment on NPC patients are essential to assess the success of NPC treatment and identify the effects on certain functional disorders. 13 Wei et al 14 study evaluated the impact of neoadjuvant chemotherapy (NACT) of various NACT cycles before radiotherapy on distant metastases and survival of patients with N2-3. The study results showed overall survival (OS), disease-free survival (DFS), local-relapse-free survival (LRFS) and distant-metastasis-free survival (DMFS) of the four-cycle NACT group was better than the two-cycle NACT group and the two-cycle NACT group patients without NACT.…”
Section: Introductionmentioning
confidence: 99%